Microwave sintering of IR-transparent Y2O3–MgO composite ceramics. Issue 5 (1st March 2023) - Permin, D.A.; Egorov, S.V.; Belyaev, A.V.; Balabanov, S.S.; Koshkin, V.A.; Boldin, M.S.; Novikova, A.V.; Timofeev, O.V.; Ladenkov, I.V.
Abstract: A method for preparation of dense Y2 O3 –MgO composite ceramics by the microwave sintering was developed. The initial powders were obtained by glycine-nitrate self-propagating high-temperature synthesis (SHS) with different oxidant-to-fuel ratio. Density and IR-transmission of microwave sintered Y2 O3 –MgO ceramics increase with respect to dispersity of the SHS-powders and reach its maximum values for the powder prepared in a 20% fuel excess. The sintering behavior of Y2 O3 –MgO compacts was investigated by optical dilatometry and measuring an electric conductivity upon heating. Significant microwave radiation power surges at temperatures of 900–1000 °C, caused by the decomposition of magnesium carbonate, have been found. As a result of matching the conditions for the synthesis of powders and sintering modes, a transmission of composite ceramics of 78% at a wavelength of 6 μm was achieved at a maximum processing temperature of 1500 °C.